2004
DOI: 10.1093/chromsci/42.3.135
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Tuning of Serially Coupled (S,S)Whelk-O 1 and (R,R)Whelk-O 1 Columns in HPLC

Abstract: The selectivity tuning of two columns coupled in series is investigated in chiral high-performance liquid chromatography. Two columns with reversal enantioselectivities [(R,R) Whelk-O 1 and (S,S) Whelk-O 1] are coupled in series via a T connector. Selectivity of such a column series is tuned by varying the mobile phase flows in the individual columns. The flow ratio necessary for the required selectivity is calculated on the basis of retention factors measured on the individual columns. The performance of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…[15,18] Also, it was observed that the system must be completely equilibrated, and the temperature controlled in order to obtain the best results. The possibilities and limitations for variation of selectivity in a column system consisting of a bonded -CN phase column and a column containing PEG crosslinked stationary phase were stated according to experimental observations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[15,18] Also, it was observed that the system must be completely equilibrated, and the temperature controlled in order to obtain the best results. The possibilities and limitations for variation of selectivity in a column system consisting of a bonded -CN phase column and a column containing PEG crosslinked stationary phase were stated according to experimental observations.…”
Section: Resultsmentioning
confidence: 99%
“…Benická et al 1456 From Eqs. [2,15] Equation 11 can be written in the form: Thus, the overall polarity of two columns coupled in series can be tuned by adjusting the mobile phase flow in the individual columns, since weight factors (x A and x B ), often called relative retentivities (F A and F B ), determine the contributions of the individual column polarities to the overall polarity of the column series.…”
Section: Theoretical Background On the Retention In Two Columns Couplmentioning
confidence: 99%
See 1 more Smart Citation
“…It was attributed to the bulkiness produced by the sulfur atoms in the reagent which resulted in steric hindrance phenomenom leading to reversal in elution order (Chen, 2005). Dungelová et al (2004) reported an interesting work by chromatographing a number of enantiomers of alkoxy substituted esters of phenylcarbamic acid on serially connected Whelk-O 1 columns that displayed reversal enantioselectivities [i.e. (R,R) and (S,S) Whelk-O 1 columns].…”
mentioning
confidence: 99%
“…(R,R) and (S,S) Whelk-O 1 columns]. It was found that fine tuning of required selectivities as well as the change in elution order of enantiomers were controlled by careful change in the flow rates of the chosen mobile phase in the individual columns (Dungelová et al, 2004). …”
mentioning
confidence: 99%